Marketing Channels of Si-Jank Pineapple Dodol at Mawar Merah Small Medium Enterprise - Susilawati, Susilawati; Harmoko, Harmoko; Mulyati, Sri (Agribusiness Department, Agriculture Faculty, Tanjungpura University, 2024)
Dodol is a typical food in Indonesia. dodol is a food product that is included in the semi-wet snack category. Each region in Indonesia has its own lunkhead characteristics. To improve sales volume and market reach, a study on the marketing channel analysis of dodol is necessary. The purpose of this research was to identify the marketing channel pattern of Si-Jank pineapple dodol at UKM Mawar Merah. The approach used in this research is descriptive quantitative and sampling by interview and analysis using margin share. The results of this study indicate: 1) The marketing channel pattern of Si-Jank pineapple dodol is twofold, namely: a) Marketing channel I (producer-consumer) and b) Marketing channel II (producer-retailer-consumer). 2) Marketing efficiency of Si-Jank pineapple dodol in UKM Mawar Merah in marketing channels I and II is already efficient, because it has a marketing efficiency value of less than 50%. UKM Mawar Merah prefer marketing channel II because the marketer's location for selling Si-Jank pineapple dodol is in the capital city of Sambas Regency, namely Sambas City, which is easily visited by consumers both from Sambas City and consumers from outside Sambas City